SPECTROSCOPY OF EPIDOTE MINERALS - Liebscher A. (My University, 2004)
Numerous spectroscopic techniques have been applied to the epidote minerals to characterize their structure and crystal chemistry. The substitution of transition metal ions Mn, Cr, and V, besides Fe, in the different crystallographic sites of epidote minerals and with different valence states has been studied by optical absorption spectroscopy. These studies mainly focused on the determination of (i) the site preferences of the different transition metal ions within the epidote minerals (e.g., Burns and Strens 1967; Tsang and Ghose 1971), (ii) the physical and structural characteristics of these sites as a function of composition, temperature and/or pressure (e.g., Taran and Langer 2000; Langer et al. 2002), (iii) their crystal field stabilization energy (e.g., Burns and Strens 1967; Langer et al. 2002), and (iv) the cause of the color and pleochroism in some epidote minerals (e.g., Faye and Nickel 1971). Major topics of infrared spectroscopic studies have been the proton environment and its changes with composition, temperature, and pressure (e.g., Langer and Raith 1974; Winkler et al. 1989; Della Ventura et al. 1996; Liebscher et al. 2002) and the phase transition within the orthorhombic solid solution series (e.g., Liebscher and Gottschalk 2004). Mossbauer spectroscopy has been used (i) to resolve the valence state of Fe in the different epidote minerals and its site location (e.g., Dollase 1973; Kartashov et al. 2002) and (ii) to study the intracrystalline Al-Fe partitioning between the different octahedral sites and the kinetic of this ordering process (e.g., Patrier et al. 1991; Fehr and Heuss-Asbichler 1997). This chapter reviews the different spectroscopic studies and techniques applied to epidote minerals with emphasis given to the crystal chemical results. An in-depth presentation and discussion of the different spectroscopic techniques and their theoretical framework is beyond the scope of this chapter. …
Keywords: epidote